IMPROVEMENT OF PEDAGOGICAL MECHANISMS OF OBSERVANCE OF CONSISTENCY AND CONTINUITY PRINCIPLES IN DEVELOPING OF YOUTH HEALTHY LIFESTYLE CULTURE - Musurmanova, Aynisa; Jamoldinova, Odinakhon (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
The current article reveals pedagogical mechanisms of  interaction among families, mahallas and educational establishments with civil society institutions in the process of developing of the culture of the youth healthy lifestyle; it substantiated the role and  significance of national pedagogy, the heritage of eastern thinkers of the Middle Ages in developing the culture of the youth healthy lifestyle; exposed the content of special course for master degree students, forming  their conviction for the necessity of operating the culture of healthy lifestyle.